Face Threatening Acts, Primary Face Threatening Acts, and the Management of Discourse: Australian English and Speakers of Asian Englishes - Conlan, Chris (John Benjamins, 2004)
Contemporary theories of linguistic politeness tend to be grounded in the pivotal concept of face threatening acts as formulated by Brown and Levinson. As a result, relatively scant attention has been paid to the ways in which politeness can also be a function of shared understandings concerning the appropriateness of discourse-staging strategies. This paper seeks to develop a perspective on linguistic politeness as it relates specifically to discourse organisation. To this end, the concept of face threatening acts (FTAs) has been augmented to introduce the notion of primary face threatening acts (PFTAs). Primary face threatening acts are seen to be speech acts by means of which pragmatic goals are ultimately attempted but which depend for their success upon being adequately framed by focussed discourse-specific and context-specific FTAs.The paper focuses on Australian English and suggests that politeness breakdowns which occur between native speakers of Australian English and speakers of English from non-Western backgroundscould well be the result of differing discourse-staging strategies. Preliminary data from research involving Thai and Japanese speakers of English and native speakers of Australian English are cited to examine this hypothesis.